Current Risk Management Practices in Psychotherapy Supervision - Mehrtens, Ilayna K.; Crapanzano, Kathleen; Tynes, L. Lee (Journal of the American Academy of Psychiatry and the Law Online, 2017)
Psychotherapy competence is a core skill for psychiatry residents, and psychotherapy supervision is a time-honored approach to teaching this skill. To explore the current supervision practices of psychiatry training programs, a 24-item questionnaire was sent to all program directors of Accreditation Council for Graduate Medical Education (ACGME)–approved adult psychiatry programs. The questionnaire included items regarding adherence to recently proposed therapy supervision practices aimed at reducing potential liability risk. The results suggested that current therapy supervision practices do not include sufficient management of the potential liability involved in therapy supervision. Better protections for patients, residents, supervisors and the institutions would be possible with improved credentialing practices and better documentation of informed consent and supervision policies and procedures.